2018
DOI: 10.1002/pmic.201800192
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling Analysis of Male Infertility inSpodoptera LituraLarvae Challenged with Azadirachtin and its Potential‐Regulated Pathways in the Following Stages

Abstract: Biopesticides are considered as an alternative to synthetic pesticide with a focus on increasing agricultural productivity as well as maintaining the ecosystem. Prior to application, its potential mechanism should be clearly addressed. Here, the effects of azadirachtin on the reproductive behavior in male Spodoptera litura (Fabricius) are determined. To further explore its molecular mechanism, an iTRAQ (isobaric tags for relative and absolute quantitation) based approach is applied to identify the differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…Our results are consistent with previous studies that demonstrated inhibited spreading of hemocytes in the greater wax moth G. mellonella on exposure to azadirachtin (Er et al, 2017) and other botanicals (Zibaee & Bandani, 2010;Zibaee et al, 2012). Based on proteomic studies, azadirachtin interfered with the regulation of cell adhesion pathways (Sun et al, 2018) and genes responsible for key steps in hormone biosynthesis (Liu et al, 2019). Considering the potent relationship between hormone signaling and the behavior of hemocytes (Nunes et al, 2021), the reduced ratio of spreading hemocytes in the current study could be related to azadirachtin-induced changes in ecdysone titers related to the regulation of immunity.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with previous studies that demonstrated inhibited spreading of hemocytes in the greater wax moth G. mellonella on exposure to azadirachtin (Er et al, 2017) and other botanicals (Zibaee & Bandani, 2010;Zibaee et al, 2012). Based on proteomic studies, azadirachtin interfered with the regulation of cell adhesion pathways (Sun et al, 2018) and genes responsible for key steps in hormone biosynthesis (Liu et al, 2019). Considering the potent relationship between hormone signaling and the behavior of hemocytes (Nunes et al, 2021), the reduced ratio of spreading hemocytes in the current study could be related to azadirachtin-induced changes in ecdysone titers related to the regulation of immunity.…”
Section: Discussionsupporting
confidence: 92%
“…The induction of apoptosis through caspase-dependent pathways by azadirachtin was also reported in S. frugiperda cultures cell line Sf9 (Shu et al, 2015). Based on proteomic studies, Sun et al (2018) reported that the molecular response mechanism of male infertility induced by azadirachtin in S. litura may be linked to regulation of many proteins in the pathway of focal adhesion exerting influences in detachment of cell attachment, the loss of cell-cell interactions, and inducing apoptosis at the pupal stage. Furthermore, many proteins in the adenosine monophosphate-activated protein kinase (AMPK) pathway were also changed at the adult stage after azadirachtin treatment as larvae (Sun et al, 2018).…”
Section: Cellular and Molecular Effectsmentioning
confidence: 77%
“…Based on proteomic studies, Sun et al (2018) reported that the molecular response mechanism of male infertility induced by azadirachtin in S. litura may be linked to regulation of many proteins in the pathway of focal adhesion exerting influences in detachment of cell attachment, the loss of cell-cell interactions, and inducing apoptosis at the pupal stage. Furthermore, many proteins in the adenosine monophosphate-activated protein kinase (AMPK) pathway were also changed at the adult stage after azadirachtin treatment as larvae (Sun et al, 2018). In D. melanogaster, a depolymerization of actin causing a cell arrest and apoptosis caspase-independent was reported after azadirachtin treatment (Anuradha et al, 2007;Anuradha and Annadurai, 2008).…”
Section: Cellular and Molecular Effectsmentioning
confidence: 99%
“…AMPK signaling is known to be activated by oxidative stress and involved in the motility parameters of human spermatozoa [ 13 16 , 60 ]. AMPK is a heterotrimeric protein, which consists of an alpha ( α ) catalytic subunit, a scaffolding beta ( β ) subunit, and a regulatory gamma ( γ ) subunit.…”
Section: Discussionmentioning
confidence: 99%